Verbal and Nonverbal Expressions of Persons Living With Dementia as Indicators of Person-Centered Caregiving. (29th January 2022) - Staehler, Maya; Benson, Clark; Block, Laura; Roberts, Tonya; Gilmore-Bykovskyi, Andrea
Abstract: Background and Objectives: Improved measures capable of capturing the influence of person-centered caregiving by staff in formal care settings on people living with dementia beyond deficit-oriented outcomes such as absence or reduction of symptoms are important for measuring progress toward improvements in well-being. This exploratory ethnographic study aimed to identify verbal and nonverbal expressions evidenced by people living with dementia surrounding person-centered caregiving approaches and to consider their use in informing temporally specific observational measures. Research Design and Methods: This study adopted a microethnographic approach through secondary analysis of 5.3 h of audiovisual observations of people living with dementia ( N = 9) in nursing home settings at mealtimes. We observed expressions surrounding person-centered caregiving approaches. A systematic review of audiovisual observations generated codes (observable indicators) of expressions that were characterized at their most discrete and unambiguous level. Results: Drawing from 82 observable verbal and nonverbal expressions by people living with dementia, 14 discrete observable indicators were identified, broadly evidencing shifts in engagement and communication. We found that people living with dementia's expressions served both responsive and initiatory communicative purposes. Discussion and Implications: Efforts to expand positive outcome measurement for people living with dementia should extend beyond characterizing them as passive respondents toward active participants in their lived experiences. Identified observable indicators can inform efforts to refine and validate measures of expressions among people living with dementia. Further research can extend this inquiry into different contexts and engage input from people living with dementia and caregivers.